2016
DOI: 10.1021/acs.macromol.6b00653
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Continuous Anion Transport Domains Using Block Copolymers Containing Phosphonium Cations

Abstract: Triblock and diblock copolymers based on isoprene (Ip) and chloromethylstyrene (CMS) were synthesized by sequential polymerization using reversible addition− fragmentation chain transfer radical polymerization (RAFT). The block copolymers were quaternized with tris(2,4,6-trimethoxyphenyl)phosphine (Ar 3 P) to prepare soluble ionomers. The ionomers were cast from chloroform to form anion exchange membranes (AEMs) with highly ordered morphologies. At low volume fractions of ionic blocks, the ionomers formed lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 102 publications
1
56
0
Order By: Relevance
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs. More specifically, pentasubstituted imidazolium (34)(35)(36)(37)(38), tetrakis(dialkylamino)phosphonium (44)(45)(46), and cobaltocenium (50,51) have shown superior alkaline stability.…”
Section: Significancementioning
confidence: 99%
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs. More specifically, pentasubstituted imidazolium (34)(35)(36)(37)(38), tetrakis(dialkylamino)phosphonium (44)(45)(46), and cobaltocenium (50,51) have shown superior alkaline stability.…”
Section: Significancementioning
confidence: 99%
“…Due to the ubiquitous application of charged polymers in polymer science, the study of their structure–property relationships has received considerable attention in the literature . Understanding the correlation between structure and polyelectrolyte properties could be used to design better ion conducting and mechanically robust polyelectrolyte membranes .…”
Section: Introductionmentioning
confidence: 99%
“…This block copolymerization has been more effective than the conventional hydrocarbon membranes, physically blended membranes, and random copolymers owing to their continuous microphase-separated morphology, and improved thermal, mechanical, and electrochemical properties. 18,19 Highlights • An organic-inorganic hybrid membrane was exploited for intermediate humidity fuel cell applications. • Sulfonated CNTs improved the water retention and other physicochemical properties of composite membranes.…”
Section: Funding Informationmentioning
confidence: 99%
“…The hydrophilic segments provide the broad interconnected hydrophilic networks responsible for the increased proton conductivity while the hydrophobic segments prevent the excessive swelling of membranes, thereby maximizing their overall performances. This block copolymerization has been more effective than the conventional hydrocarbon membranes, physically blended membranes, and random copolymers owing to their continuous microphase‐separated morphology, and improved thermal, mechanical, and electrochemical properties …”
Section: Introductionmentioning
confidence: 99%